Analisis kelayakan finansial usaha pembuatan perahu fiber di Desa Tanjung Bunga Kecamatan Wawolesea Kabupaten Konawe Utara - Nasari, Mainar; Yusuf, Sarini; Rosmawati; Siang, Roslindah Daeng; Riani, Irdam; Risfandi (Jurnal Sosial Ekonomi Perikanan, 2022)
This study aims to determine the benefits and financial feasibility of fiber boat building business in Tanjung Bunga Village, Wawolesea District, North Konawe Regency South East Sulawesi. The population and samples in this study were all fiber boat building business owners that consisted of 2 people. The data analysis used was quantitative analysis using the formula of fixed, variable and total costs. Revenues, profits and financial analysis were done using 5 criteria that were R/C Ratio, Net Present Value, Investment Rate of Return, Payback Period and Break Even Point. The results of the analysis showed that the fiber boat building business earned an annual profit of IDR510,450,574/year with an R/C Ratio of 1.82. By using a discount factor of 17%, the Net Present Value was IDR789,537,629/year with an Investment Rate of Return of 40% and a Payback Period of 1. Break Even Point was achieved after the production of 28 units at a price of IDR12,384,434/year. This study showed that the fiber boat building business in the study site was profitable and feasible.